PEMBELAJARAN PIDATO SECARA DARING PADA SISWA SEKOLAH DASAR - Pudji Susanti (STKIP Siliwangi, 2022)
The Covid-19 outbreak has affected all areas of life in the world, including education. In order for teaching and learning activities to continue, the government issued one policy, namely distance learning through online or online. This study aims to describe the implementation of online learning in Indonesian subjects with speech material for sixth grade elementary school students. This research was conducted using descriptive methods with qualitative descriptive analysis techniques. Data collection techniques through interviews and observation. Because the learning conditions were still online, interviews were conducted online using the Google Form application. The sample of this study was the sixth grade students of SDN 2 Mangunrejo Grobogan, Central Java, totaling 19 students. The results of the study indicate that online learning in the Indonesian language subject of speech material runs according to the lesson plan. Based on the results of observations and interviews, it showed that students quite liked and were quite easy to accept the material presented during online learning. However, there are still some obstacles experienced by students that cannot be ignored during learning such as difficult networks or signals, waste of quota, technology stuttering, boredom, and students tend to prefer face-to-face.